2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24660
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on Reflection: How Educators Experience the Opportunity to Talk About Supporting Student Reflection

Abstract: To explore the general question of ways to help educators become more reflective, this paper focuses on the proposition that one way to help educators be more reflective is to give them an opportunity to discuss (or be interviewed about) an activity they do with students. To address this proposition, we use a "multiple perspectives methodology" featuring essays from seven educators about their experiences of being interviewed about a reflection activity they have done with students. The educators' essays sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Recently the Consortium to Promote Reflection in Engineering Education (CPREE) and its constituents have made considerable progress in promoting and studying the use of reflection across the engineering education community within the United States [9][10][11][12][13][14][15][16]. Research has observed that the value of reflection within an educational or work environment can vary and that many are not aware of the research and applied professional skills that support reflective practice [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the Consortium to Promote Reflection in Engineering Education (CPREE) and its constituents have made considerable progress in promoting and studying the use of reflection across the engineering education community within the United States [9][10][11][12][13][14][15][16]. Research has observed that the value of reflection within an educational or work environment can vary and that many are not aware of the research and applied professional skills that support reflective practice [15].…”
Section: Introductionmentioning
confidence: 99%
“…Drawing from examples of collaborative inquiry and multiple perspectives methodology from engineering education literature 15,17,18 , we wanted to balance the intricacies of the individual stories with the overarching themes that arose by bringing together multiple perspectives from different areas of research. 17 In the next section, each author was asked to share the story of their experience with SOI in their own words, with the aim of providing readers an opportunity to "'experience' a set of key ideas while also coming 'into contact with...different languages, modes of communication, and forms of inquiry" 17 (p.51).…”
Section: Telling the Storymentioning
confidence: 99%
“…Faculty involved with CPREE are promoting the use of reflection activities and assignments on their campuses and are engaging their colleagues in conversations about the benefits of reflection in education. 2 CPREE has amassed a large database of reflection activities and assignments from these faculty in their National Field Guide, which can be accessed on their website, www.cpree.uw.edu. Here educators can find examples of reflective practices across the CPREE partner institutions, which can be used in conjunction with supportive literature to sell other faculty on the educational benefits and gains in student learning.…”
Section: Introductionmentioning
confidence: 99%
“…Turns et al 2 noted this gap and suggested we go beyond engineering education -medical schools, nursing schools, and teacher education -to gain an understanding of how other professions view and utilize reflection. Further research is clearly needed to understand the use of reflection in engineering education.…”
mentioning
confidence: 99%